Impact of ridge nitrogen and furrow irrigation strategies to evaluation winter wheat production and economic benefits under bed-planting in semi-humid regions - Yanhao Lian; Chunlong Li; Pengbin Han; Shahzad Ali; Yongzhe Ren; Tongbao Lin; Zhiqiang Wang; Sen Li (Agricultural Water Management)
To further explore the water and nitrogen-saving potential technique under the ridge-nitrogen and furrow irrigation model of winter wheat. The study consists of four nitrogen treatments: F0: no nitrogen; F1: 120 kg N hm−2 (100 % conventional urea); F2: 180 kg N hm−2 (30 % conventional urea and 70 % stabilized urea), and F3: 240 kg N hm−2 (components is same as F2); while three irrigation levels of (I1: 300; I2: 450 and I3: 600 m hm−2) during 2020–2021 and 2021–2022. The results showed that increasing the nitrogen application rate was beneficial to nitrogen uptake, plant growth, and yield formation under the bed planting technique, while the nitrogen application rate exceeded 180 kg ha−1, the grain yield and nitrogen accumulation had no significant increase. The soil moisture at the maturity stage under the ridge cultivation gradually decreases with the increase of nitrogen application. The economic benefits and output-input ratio reached the highest level under the F2I2 treatment. The nitrogen uptake efficiency, nitrogen partial fertilizer productivity, and nitrogen agronomy efficiency under the F2I2 treatment increased by 21.7 %, 29.1 %, and 2.9 % respectively, and the IWUE, PWUE, and WUE increased by 61.0 %, 3.4 %, and 12.3 % compared with conventional practice. The yield, net income, and output-input ratio increased by 5.2 %, 8.3 %, and 20.1 % compared with conventional practice. Therefore, controlled-release urea at the 180 kg N ha−1 and bed planting technique combined with 450 m hm−2 irrigation could improve nitrogen and irrigation use efficiency; maintain high grain yield and economic benefit.